Polishing solution for chemical mechanical polishing of Cu wiring Co barrier layer integrated circuit

By using amino acid reagents and imidazolidinyl urea in the CMP polishing liquid, combining H2O2 and nanosilicon dioxide, the efficient selective polishing of the Cu/Co barrier layer is achieved, and the problems of polishing rate selectivity and interface corrosion control in the prior art are solved, and the nano-level surface quality and high reliability are achieved.

CN119592230APending Publication Date: 2025-03-11HEBEI UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411919267.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing CMP polishing liquid is difficult to meet the polishing rate selectivity and interface corrosion control requirements of copper and cobalt barrier layers at the same time, resulting in surface defects and galvanic corrosion problems.

Method used

The polishing solution of the Cu/Co barrier layer is achieved by combining chemical dissolution and mechanical friction by combining chemical dissolution with mechanical friction.

Benefits of technology

The Cu/Co removal rate selection ratio is close to 1:1, which significantly reduces surface defects and galvanic corrosion, ensures nano-scale surface roughness and high reliability, and is suitable for advanced process processes of multi-layer interconnect structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592230A_ABST
    Figure CN119592230A_ABST
Patent Text Reader

Abstract

The invention relates to a polishing solution suitable for chemical mechanical polishing of a Cu wiring Co barrier layer integrated circuit. The polishing solution comprises the following components: silica sol, an oxidizing agent, a complexing agent, a corrosion inhibitor and deionized water, the pH value of the polishing solution is 8.0 to 10.0. According to the polishing solution, an amino acid reagent harmless to the environment is selected as a complexing agent, reagents such as imidazoline and imidazolidinyl urea are adopted as inhibitors, H2O2 is adopted as an oxidizing agent, silica sol is adopted as a grinding material, and the chemical dissolution effect and the mechanical effect are combined together to achieve global planarization of the wafer surface. Efficient CMP of a Cu / Co barrier layer is achieved, after the polishing solution is used for polishing the surface of a wafer, the Cu / Co removal rate selection ratio is close to 1: 1, and the effect that the surface roughness reaches the nanoscale can be achieved, so that the strict requirement of integrated circuit manufacturing for the CMP process is met, and the preparation process is simple and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an alkaline polishing liquid used for chemical mechanical polishing (CMP) in the field of chip manufacturing and a preparation method thereof, in particular to an alkaline polishing liquid suitable for a Cu / Co barrier layer and a preparation method thereof. Background Art

[0002] As the semiconductor process enters the 14nm and below nodes, the number of metal interconnect layers increases significantly, and the wire spacing and size are further reduced, but the thickness of the high-resistivity Ta / TaN double-layer barrier used for Cu interconnects remains almost unchanged. Due to the high technical difficulty of further thinning the nanoscale barrier layer and the impact on device reliability, the proportion of Ta / TaN in the cross-sectional area after the wire is reduced increases. Because Co has low resistivity, low hardness, high adhesion and good wettability, and can achieve conformal deposition in high aspect ratio grooves, Co is introduced as a new barrier layer material. The application of Co not only helps to thin the barrier layer, increase the proportion of metal layer copper in the conductive channel, but also simplifies the process flow. However, the introduction of Co also poses new challenges to the chemical mechanical polishing (CMP) of the barrier layer, and it is urgent to carry out comprehensive research to screen CMP polishing liquids suitable for Co-based barrier layers in multi-layer Cu interconnects.

[0003] CMP is one of the important process steps to achieve multi-layer wiring. It is the key global planarization technology for high-density integration of current integrated circuits. It combines the chemical and mechanical effects of the polishing liquid to achieve surface planarization through chemical corrosion and mechanical friction. The CMP process requires selective removal of the Cu and Co barrier layers to ensure the final planarization effect. The polishing liquid for the Cu / Co structure needs to have excellent polishing performance, which is mainly manifested in the following characteristics:

[0004] 1. High selectivity: It can precisely control the polishing rate of copper and cobalt barrier layers, achieve surface consistent removal, and inhibit the generation of surface defects such as dishing pits.

[0005] 2. Low surface defects: After polishing, surface defects such as scratches and pits should be minimized to ensure the electrical performance of the device.

[0006] 3. Low galvanic corrosion: It can control the galvanic corrosion between Cu / Co and ensure the signal transmission performance and electromigration reliability.

[0007] Most of the existing CMP polishing liquids are designed for a single material, and it is difficult to simultaneously meet the requirements of polishing rate selectivity and interface corrosion control for copper and cobalt barrier layers. For example, the invention patent CN112322190A discloses a multilayer copper interconnect barrier layer polishing liquid and its preparation method, the main components of which are silica sol, FA / OⅡ, divalent copper ions and FA / O, and the Cu removal rate is improved by chelation; its polishing effect can meet the polishing requirements of Cu in the barrier layer, but the polishing liquid does not take into account the simultaneous removal of the interconnect layer and the barrier layer materials. The invention patent CN111748286A discloses a metal cobalt polishing liquid, the main components of which are L-aspartic acid and glutathione, and the combined action of the two achieves the removal of Co, but the polishing liquid only focuses on the polishing rate of Co in the barrier layer, and does not obtain a good Cu / Co removal rate selectivity ratio. In addition, the chemical components in some polishing liquids can cause pits on the copper surface, or the cobalt barrier layer is over-polished, thereby reducing the overall performance of the wiring.

[0008] Therefore, developing a polishing solution with high efficiency, stability and environmental protection for Cu / Co barrier layer has become a research hotspot and technical difficulty in the field of CMP process technology. Summary of the invention

[0009] The purpose of the present invention is to provide a polishing liquid for chemical mechanical polishing of Cu wiring Co barrier layer integrated circuits in view of the limitations of current technologies. The polishing liquid uses amino acid reagents that are harmless to the environment as complexing agents, uses imidazoline, imidazolidinyl urea and other reagents as inhibitors, uses H2O2 as an oxidant, and uses silica sol as an abrasive, and combines chemical dissolution with mechanical action to achieve global flattening of the wafer surface. The present invention achieves efficient CMP of the Cu / Co barrier layer. After the wafer surface is polished using the polishing liquid of the present invention, the Cu / Co removal rate selection ratio is close to 1:1, and the surface roughness can reach the nanometer level, thereby meeting the strict requirements of integrated circuit manufacturing for the CMP process. The preparation process is simple and suitable for industrial production.

[0010] The technical solution of the present invention is:

[0011] A polishing liquid suitable for chemical mechanical polishing of Cu wiring Co barrier layer integrated circuits, the polishing liquid composition includes the following, calculated by mass percentage:

[0012] Nano silicon dioxide: 5-10wt%

[0013] Oxidant: 0.15-0.75wt%

[0014] Complexing agent: 0.1-0.7wt%

[0015] Corrosion inhibitor: 0.1-0.5wt%

[0016] Deionized water: balance

[0017] The sum of the component proportions is 100%; the pH value of the polishing liquid is 8.0-10.0.

[0018] The complexing agent is one or more of cysteine, threonine, aspartic acid, glutamic acid, histidine, lysine, serine, methionine, tyrosine, proline, phenylalanine, cystine, proline, and tryptophan.

[0019] The corrosion inhibitor is one or more of imidazolidinyl urea, imidazoline, diimidazolidinyl urea, diethyl diurea, methyl imidazolidinyl urea, trifluorochlorothioxanthene, phenoxyethanol, chlorphenesin, and hexamethylenetetramine.

[0020] The oxidant is hydrogen peroxide (H2O2).

[0021] The average particle size of the silica sol is 60-70 nm, the SiO2 concentration is 40 wt%, and the dispersion is maintained within ±5%.

[0022] The pH regulator is analytical pure nitric acid and potassium hydroxide, which are used after dilution, and the pH adjustment method is titration.

[0023] The polishing preparation method suitable for chemical mechanical polishing of Cu wiring Co barrier layer integrated circuits comprises the following steps:

[0024] The complexing agent, corrosion inhibitor, silica sol and oxidant are sequentially added into deionized water according to the ratio, and the polishing liquid is obtained after stirring. The polishing liquid is first ultrafiltered with a 600nm pore size filter element, and then ultrafiltered with a 400nm pore size filter element, and stirred under vacuum negative pressure conditions. The stirring speed is controlled at 60-80 rpm, the stirring time is 2-15 minutes, and the temperature is maintained at 15-25°C; in addition, the pH value of the solution is adjusted by titration.

[0025] The essential features of the present invention are:

[0026] Through the joint action of oxidants, complexing agents, inhibitors and other components, efficient and selective polishing of the cobalt barrier layer is achieved. H2O2 reacts with the copper and cobalt surfaces to generate oxide films and then metal ions; amino acid complexing agents work together with their own amino and carboxyl groups to combine with metal ions to form stable complexes, thereby increasing the removal rate of Cu and Co. The inhibitor is adsorbed on the metal surface with the help of its own heterocyclic structure to form a protective film, inhibit excessive corrosion, and reach a dynamic equilibrium with the oxidant during the reaction process. The precise control of metal surface corrosion is achieved through the joint action of oxidants, complexing agents and inhibitors. Abrasive silica sol is used as a physical polishing medium. Through the mechanical friction of its particles, it preferentially removes the metal oxide film at high places, further optimizes the surface flatness, and ensures the nano-level quality of the polished surface. The components work together under chemical reactions and mechanical actions, making the removal rate selectivity of copper and cobalt controllable and the surface quality excellent, reflecting the significant advantages of the present invention in precise selective control and green environmental protection processes.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] High selectivity: The polishing liquid of the present invention achieves highly selective polishing of copper and cobalt barrier layers by optimizing the formula, can effectively control the removal rates of the two materials, and achieves adjustable and controllable removal rates, thereby significantly improving the polishing accuracy.

[0029] Low galvanic corrosion: The polishing liquid of the present invention reduces the corrosion potential difference between the copper and cobalt barrier layers to less than 10mv by optimizing the electrochemical equilibrium mechanism. During the polishing process, the present invention inhibits the corrosion reaction caused by the potential difference between the two materials, thereby reducing excessive material removal and surface damage, and further improving the surface quality and reliability after polishing. This feature is particularly suitable for advanced process technologies with high requirements for material integrity in multi-layer interconnect structures.

[0030] Low surface defects: The polishing liquid of the present invention can make the wafer have good surface quality during polishing, significantly reduce scratches, pits and other defects on the wafer surface, ensure the flatness and uniformity of the surface after polishing, and help improve the reliability of integrated circuit devices. After being treated with the polishing liquid of the present invention, the surface roughness of the wafer can reach the nanometer level, meeting the strict requirements of advanced semiconductor manufacturing processes for surface quality.

[0031] Environmentally friendly: The polishing liquid of the present invention adopts an environmentally friendly complexing agent, which reduces pollution to the environment, optimizes the stability and repeatability of the chemical composition, and reduces the loss of the process to the equipment and the environment.

[0032] High cost-effectiveness: It uses domestic raw materials with high cost-effectiveness, and the usage of each ingredient in the formula is reasonable, which helps to reduce production costs and has good potential for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 , Surface roughness image of Cu after chemical mechanical polishing in Example 1;

[0034] Figure 2 , Surface roughness image of Co after chemical mechanical polishing in Example 1;

[0035] Figure 3 , Surface roughness image of Cu after chemical mechanical polishing in Example 2;

[0036] Figure 4 , Surface roughness image of Co after chemical mechanical polishing in Example 2;

[0037] Figure 5 , Surface roughness image of Cu after chemical mechanical polishing in Example 3;

[0038] Figure 6 , Surface roughness image of Co after chemical mechanical polishing in Example 3;

[0039] Figure 7 , Surface roughness image of Cu after chemical mechanical polishing in Example 4;

[0040] Figure 8 , Surface roughness diagram of Example 4Co after chemical mechanical polishing. Specific embodiments

[0041] Comparative Example 1

[0042] Process conditions: Use the configured polishing liquid in the Alpsitec-E460E polishing machine; the working pressure is 1.5psi; the disc speed is 93 rpm, the polishing head speed is 87 rpm, the polishing liquid flow rate is 300ml / min, and the 300mm copper-plated film is polished, then rinsed with deionized water and dried with nitrogen.

[0043] Polishing liquid formula: take 250g of silica sol with an abrasive mass fraction of 40%, a particle size of 50nm-90nm, and a dispersion of ±3%; 7.5g of FA / O type II chelating agent; 10g of FA / O surfactant; 15g of copper glycinate; 40% KOH or 10% nitric acid as a pH regulator.

[0044] Experimental results: The removal rate of Cu is

[0045] Comparative Example 2

[0046] Process conditions: Using the CP-4 machine, a 2-inch cobalt disc was glued to the polishing head through wax. The polishing parameters were set as follows: Politex polishing pad; polishing pressure was 3psi; polishing pad speed was 90rpm; polishing disc speed was 90rpm; polishing liquid flow rate was 125mL / min; polishing time was 10min. After each polishing, the polishing pad was cleaned with water for 5 minutes, and the polished disc was ultrasonically cleaned in the cleaning liquid for 10 minutes and then dried with nitrogen.

[0047] Polishing liquid formula: 80nmSiO2+0.15%L-aspartic acid+0.1%H2O2+0.15%glutathione, pH=10

[0048] Experimental results: The removal rate of Co is

[0049] Example 1

[0050] Implementation conditions: Use Huahai Qingke U300B polishing machine, equipped with polishing pad Politex REG pad, polishing at a working pressure of 1.5psi, with a polishing disc speed of 93 rpm, a polishing head speed of 87 rpm, and a polishing liquid flow rate of 300ml / min, then rinse with deionized water and blow dry with nitrogen. Table 1 shows the polishing liquid 1-4 of the present invention. The polishing liquid is prepared according to the formula given in the table, and KOH or HNO3 is used to adjust to the required pH value. A four-probe tester (Four Dimensions, Inc, 333A) is used to measure the amount of metal film removed before and after polishing to obtain the removal rate of the target material, and an atomic force microscope (AFM) 5600LS produced by Agilent is used to measure the morphology and roughness of the wafer surface. A Mettler electronic analytical balance (ME204E, accuracy 0.0001g) is used for reagent weighing.

[0051] Polishing liquid formula: 5wt% SiO2+0.6wt% H2O2+0.3wt% cysteine+0.1wt% imidazolidinyl urea, pH 9;

[0052] Polishing liquid preparation:

[0053] 1. Weigh 3 g of cysteine ​​(Cys, analytical grade) and add it to 100 g of deionized water while stirring to obtain solution 1.

[0054] 2. Weigh 1 g of imidazolidinyl urea (UI, analytical grade), add it to 20 g of deionized water to dissolve it, and obtain solution 2. Pour solution 2 into solution 1 and mix them to obtain solution 3.

[0055] 3. Weigh 250g of silica sol (the main component is nano-silicon dioxide, with an average particle size of 60-70nm, a SiO2 concentration of 40wt%, and a dispersion degree between ±5%) and add it to 2 volumes of deionized water while stirring to prepare a diluted silica sol solution and mix it with solution 3 to obtain solution 4.

[0056] 4. Weigh 20 g of a 30% by mass aqueous hydrogen peroxide solution, add it to solution 4, and stir evenly to obtain solution 5.

[0057] 5. Add deionized water to make the total weight close to 950g. Add dilute nitric acid and potassium hydroxide (30% by mass, as pH adjuster) by titration to accurately adjust the pH value of the solution to 10. Make up the balance to 1000g with deionized water.

[0058] 6. Then, stir under vacuum and negative pressure, the speed should be controlled between 60-80 rpm, and the stirring time should last for 2-15 minutes. At the same time, the temperature should be maintained at 15-25℃.

[0059] 7. The mixed solution is subjected to two-stage ultrafiltration treatment using filter elements with pore sizes of 600 nm and 400 nm in sequence. After completion, a polishing solution is obtained.

[0060] Experimental results: The removal rate of Cu is The removal rate of Co is The selection ratio of the removal rate is 1:1.04.

[0061] Embodiment 2-4

[0062] The other steps are the same as those in Example 1, and the changes in the contents of the relevant materials are shown in Table 1.

[0063] Table 1, Example 1-Example 4 polishing liquid formula

[0064]

[0065]

[0066] Cys: cysteine; Thr: threonine; IU: imidazolidinyl urea; IM: imidazoline.

[0067] Table 2, Example 1-Example 4 effect data

[0068]

[0069] Through Example 1 and Figure 1 and Figure 2It can be seen that when cysteine ​​and imidazolidinyl urea are used simultaneously, the removal rate selection ratio is 1:1.04, at which time the removal rates of Cu and Co are moderate and the surface roughness is low. Figure 5 , Figure 6 It can be seen that the joint action of threonine and imidazoline can not only accurately regulate the Cu / Co removal rate selectivity, but also obtain good surface quality. It can be seen from the experimental test data of comparative examples 1, 2 and embodiments 1-embodiment 4 that the polishing liquid of the comparative example cannot take into account the removal rates of Cu and Co at the same time and may cause the selectivity to be difficult to regulate. The polishing liquid of the present invention shows a stable and efficient removal rate in removing copper and cobalt, and has a Cu / Co removal rate selectivity close to 1:1 (ranging from 1:1.02 to 1:1.04). This good selectivity control can meet the strict requirements for the selective removal of metal layers and barrier layers during chemical mechanical polishing. In addition, the surface roughness of the wafer after polishing is controlled below the nanometer level, wherein the roughness of Cu is in the range of 0.140 to 0.993nm, and the roughness of Co is in the range of 0.152 to 0.810nm, indicating that the surface quality is excellent and the damage is small.

[0070] The present invention provides a novel chemical mechanical polishing (CMP) liquid, which uses silica sol as an abrasive, an amino acid reagent as a complexing agent, an imidazolidinyl urea reagent as a corrosion inhibitor, and hydrogen peroxide as an oxidant. In the integrated circuit manufacturing process, this polishing liquid can effectively realize efficient polishing of metal surfaces and meet the strict requirements on surface quality and removal rate selectivity. Through a comprehensive analysis of the functions of different components, the polishing liquid of the present invention exhibits excellent performance and has unique advantages.

[0071] First, when the silica sol with an average particle size of 60-70nm is used as an abrasive in the CMP process, its particles will not cause excessive damage to the wafer surface, and have a low viscosity, which is conducive to reducing the surface roughness after polishing. Secondly, amino acid reagents play an important role in the removal rate and surface quality control of metals as complexing agents. Amino acid compounds have excellent metal complexing ability. Through their amino and carboxyl groups, they form stable complexes with metal ions, which can accurately control the dissolution rate of metals, especially the selective removal of copper and cobalt. The green environmental protection of amino acid reagents is also an important advantage of them as complexing agents. They have good biodegradability and will not cause pollution to the environment, which meets modern environmental protection requirements. The use of imidazole reagents as corrosion inhibitors enables this polishing liquid to better protect the metal surface during the polishing process and avoid unnecessary corrosion. In addition, imidazole compounds have excellent corrosion inhibition properties and can form a protective film on the metal surface to inhibit excessive reaction between oxidants and metal surfaces, thereby reducing metal corrosion and dissolution. They can physically adsorb to the metal surface, especially for copper and cobalt. The protective effect is particularly significant. Moreover, imidazole reagents have good stability in a wide pH range and are suitable for polishing liquids of various formulations, which enhances the overall chemical stability. Its low toxicity and pollution-free characteristics make it in line with the concept of green chemistry and suitable for industrial production. Finally, hydrogen peroxide is an economical, environmentally friendly and efficient oxidant. The addition of hydrogen peroxide effectively improves the efficiency of metal removal and can remove the oxide layer in a shorter time, ensuring that the wafer surface is flat and smooth.

[0072] Through the analysis of the above components, the polishing liquid of the present invention shows high selectivity, low defect rate and good compatibility, and can meet the strict requirements of CMP process in integrated circuit manufacturing. The surface roughness of the wafer after polishing can be controlled at the nanometer level, and has excellent surface quality. By adjusting the concentration of the oxidant, the metal removal rate and selectivity can also be flexibly controlled to ensure accurate polishing of different materials. In summary, the polishing liquid of the present invention not only has excellent performance, but also meets the requirements of environmental protection and green chemistry, is suitable for large-scale industrial production, and has broad application prospects.

[0073] The specific embodiments of the present invention are described in detail above, but they are only examples, and the present invention is not limited to the specific embodiments described above. For those skilled in the art, any equivalent modifications and substitutions made to the present invention are also within the scope of the present invention.

[0074] Matters not covered by the present invention are known technologies.

Claims

1. A polishing liquid suitable for chemical mechanical polishing of Cu wiring Co barrier layer integrated circuits, characterized in that the polishing liquid comprises the following components, calculated by mass percentage: Nano silicon dioxide: 5-10wt% Oxidant: 0.15-0.75wt% Complexing agent: 0.1-0.7wt% Corrosion inhibitor: 0.1-0.5wt% Deionized water: balance The pH of the polishing liquid is 8.0-10.0; The complexing agent is one or more of cysteine, threonine, aspartic acid, glutamic acid, histidine, lysine, serine, methionine, tyrosine, proline, phenylalanine, cystine, proline, and tryptophan; The corrosion inhibitor is one or more of imidazolidinyl urea, imidazoline, diimidazolidinyl urea, diethyl diurea, methyl imidazolidinyl urea, trifluorochlorothioxanthene, phenoxyethanol, chlorphenesin, and hexamethylenetetramine.

2. The polishing liquid suitable for chemical mechanical polishing of Cu wiring Co barrier layer integrated circuit as claimed in claim 1, characterized in that The oxidant is hydrogen peroxide (H2O2).

3. The polishing liquid suitable for chemical mechanical polishing of Cu wiring Co barrier layer integrated circuits as described in claim 1 is characterized in that the average particle size of the silica sol is 60-70nm, the SiO2 concentration is 40wt%, and the dispersion is maintained within ±5%.

4. The preparation method for chemical mechanical polishing of Cu wiring Co barrier layer integrated circuits as claimed in claim 1, characterized in that The following steps are involved: The complexing agent, corrosion inhibitor, silica sol and oxidant are sequentially added into deionized water according to the said ratio, and the polishing liquid is obtained after stirring. The polishing liquid is firstly ultrafiltered by a 600nm pore size filter element, and then ultrafiltered by a 400nm pore size filter element, and stirred under vacuum negative pressure conditions, the stirring speed is controlled at 60-80 rpm, the stirring time is 2-15 minutes, and the temperature is maintained at 15-25°C; in addition, the pH value of the solution is adjusted by titration.

5. The preparation method for chemical mechanical polishing of Cu wiring Co barrier layer integrated circuits as claimed in claim 4, characterized in that the pH regulator is nitric acid and potassium hydroxide.

Citation Information

Patent Citations

  • Metal cobalt polishing solution and application thereof

    CN111748286A

  • Multi-layer copper interconnection barrier layer polishing solution and preparation method thereof

    CN112322190A